Polymnia Siegesbeckia D.C.: PROPAGAÇÃO VEGETATIVA (NOTA PRELIMINAR) - Piccolo, Antonia Lélia G.; Thomazini, Lilian I.; Massa, Celia S. (REVISTA DE AGRICULTURA, 2016)
Polymnia Siegesbeckia D.C.: PROPAGAÇÃO VEGETATIVA (NOTA PRELIMINAR)